2019
DOI: 10.1007/s12665-019-8506-7
|View full text |Cite
|
Sign up to set email alerts
|

Stability and characterisation of spoil heaps in European surface lignite mines: a state-of-the-art review in light of new data

Abstract: The large amount of spoil material produced during the mining process imposes a significant economic and environmental liability on lignite producers. In this context, the present paper provides an overview of the geotechnical characteristics of European lignite mine spoil heaps and discusses their significance to the stability of the heaps. In order to achieve this, samples collected from spoil heaps of Polish, Czech and Greek mines are analysed and the results are compiled with data from the literature. A ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Engineering such as tunnel excavation will produce a large amount of spoil which is a kind of waste, the stacking of spoil will occupy land, cause environmental pollution [1], and form the source causing landslides [2,3]. Some tunnel spoil cannot be recycled into concrete due to the risk for AAR [4].…”
Section: Introductionmentioning
confidence: 99%
“…Engineering such as tunnel excavation will produce a large amount of spoil which is a kind of waste, the stacking of spoil will occupy land, cause environmental pollution [1], and form the source causing landslides [2,3]. Some tunnel spoil cannot be recycled into concrete due to the risk for AAR [4].…”
Section: Introductionmentioning
confidence: 99%
“…A hazard related to the loss of slope stability in lignite mines is a significant problem considered in the context of the majority of mining works (Masoudian et al, 2019). As a consequence, most of the large surface mining operations around the world are integrating various instruments in extensive slope monitoring programs undertaken as part of their mine performance monitoring systems (Carla et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…They are significantly heterogeneous, not subjected to standard soil norms, and typical geotechnical evaluations should be applied with caution. Masoudian et al (2019) presented an overview of several European lignite mine spoil heaps' geotechnical properties and concluded that they indicate a remarkable variability (more considerable than typical in situ soils). It is noteworthy that the heterogeneity of spoil materials is not only affected by natural processes, but also by the spoil's transportation method (belt conveyor vs haul trucks); the dumping method (spreaders vs trucks, and top-down with an angle of repose vs bottom-up in layers); the different origin of the soils (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ulusay et al 1996; Dawson et al 1998;Steiakakis et al 2009;Poulsen et al 2014). Although several studies exist relating to spoil heaps' slope stability, very few include detailed geotechnical characterization of the spoil material (Okagbue 1984; Ulusay et al 1995;Skarzyńska and Michalski 1998;Cadierno et al 2014;Fityus et al 2014;Li et al 2016; Masoudian et al 2019). A more in-depth analysis will lead to better insights, improved analysis, and safer, cost-effective, and sustainable design.…”
Section: Introductionmentioning
confidence: 99%